Case report: Conquer a complex variant: Coronary-pulmonary artery fistulas, atrial septal defect and bicuspid pulmonary valve, under beating heart surgery - Zhou, Ting; Liu, Chaobing; Zhang, Songlin (Frontiers in Cardiovascular Medicine, 2022)
Coronary artery to pulmonary artery fistula (CPAF) is a congenital or acquired abnormal channel between arteries, with a left-to-right cardiac shunting, which may lead to myocardial ischemia, arrhythmia, thrombotic complications, and heart failure. CPAF is usually detected by coronary angiography but few reports have used beating-heart surgery as a detection method. The patient in this case report is a 39-year-old male diagnosed with atrial septal defect (ASD), bicuspid pulmonary valve, and moderate tricuspid regurgitation (TR). He is asymptomatic. In preoperative evaluation, significant CPAF was suspected using echocardiography. The patient refused coronary angiography due to allergic history. Therefore, the cardiac team designed and performed on-pump beating-heart surgery (OPBHS) to detect and repair these disorders, and suggested OPBHS as a myocardial protection strategy for the patient at low surgical risk. A rare and complex cardiovascular case with CPAFs from two branches of the left anterior descending coronary (LAD) artery to the main pulmonary artery (MPA) with ASD, bicuspid pulmonary valve, and moderate TR has not yet been reported in the literature, and its embryological hypothesis has been further analyzed in this report.